A nationwide retrospective observational study of population newborn screening for medium‐chain acyl‐CoA dehydrogenase (MCAD) deficiency in the Netherlands. Issue 5 (16th May 2019) - Jager, Emmalie A.; Kuijpers, Myrthe M.; Bosch, Annet M.; Mulder, Margot F.; Gozalbo, Estela R.; Visser, Gepke; de Vries, Maaike; Williams, Monique; Waterham, Hans R.; van Spronsen, Francjan J.; Schielen, Peter C. J. I.; Derks, Terry G. J.
Abstract: To evaluate the Dutch newborn screening (NBS) for medium‐chain acyl‐CoA dehydrogenase (MCAD) deficiency since 2007, a nationwide retrospective, observational study was performed of clinical, laboratory and epidemiological parameters of patients with MCAD deficiency born between 2007 and 2015. Severe MCAD deficiency was defined by ACADM genotypes associated with clinical ascertainment, or variant ACADM genotypes with a residual MCAD enzyme activity <10%. Mild MCAD deficiency was defined by variant ACADM genotypes with a residual MCAD enzyme activity ≥10%. The prevalence of MCAD deficiency was 1/8300 (95% CI: 1/7300‐1/9600). Sensitivity of the Dutch NBS was 99% and specificity ~100%, with a positive predictive value of 86%. Thirteen newborns with MCAD deficiency suffered from neonatal symptoms, three of them died. Of the 189 identified neonates, 24% had mild MCAD deficiency. The acylcarnitine ratio octanoylcarnitine (C8)/decanoylcarnitine (C10) was superior to C8 in discriminating between mild and severe cases and more stable in the first days of life. NBS for MCAD deficiency has a high sensitivity, specificity, and positive predictive value. In the absence of a golden standard to confirm the diagnosis, the combination of acylcarnitine (ratios), molecular and enzymatic studies allows risk stratification. To improve evaluation of NBS protocols and clinical guidelines, additional use of acylcarnitine ratios and multivariate pattern‐recognition software may be reappraised in the Dutch situation. Prospective recording of NBS and follow‐up data is warranted covering the entire health care chain of preventive and curative medicine.